Konflik Kewenangan Penyidik Polisi Republik Indonesia dan Penyidik Badan Narkotika Nasional Dalam Menangani Tindak Pidana Narkotika - Verdy Krishna; Ferry Anggriawan (MLJ Merdeka Law Journal, 2023)
This article aims to examine the authority of Polri investigators and National Narcotics Agency investigators in handling narcotics crimes and the regulation of the authority of Police Investigators and National Narcotics Agency investigators in handling narcotics crimes in the future. This research is normative, or doctrinal, juridical legal research which is also referred to as library research or document study, because it is mostly carried out on secondary data. The results of the research show that regarding the authority given by Law No. 35 of 2009 concerning Narcotics to investigators in handling narcotics crimes based on Article 75 of Law No. 35 of 2009 concerning Narcotics, it creates a blurring of norms, because it only includes the phrase BNN investigators are authorized so that the authority in article 75 of Law No. 35 of 2009 concerning narcotics, it is as if only BNN investigators own it. Based on article 81 of Law No. 35 of 2009 concerning narcotics, BNN investigators and National Police investigators are given the authority to enforce non-narcotics crime laws. So it is necessary to make judicial changes to article 75 of Law No. 35 of 2009 concerning Narcotics by removing the phrase BNN Investigators become Investigators so that there is no longer any legal ambiguity regarding who has the authority to implement the provisions in article 75 of Law No. 35 of 2009 concerning Narcotics .